Development and software piracy - Francisco Martínez-Sánchez; Andrés Romeu (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
In this paper, the authors analyze the differences in piracy rates from one country to another. Like previous papers on the topic, they find that more developed countries have lower incentives for pirating. Unlike previous papers, they find that the piracy rate is positively correlated with the tax burden rate but negatively correlated with the domestic market size and exports over GDP. The authors also separate the impacts of education and R&D on piracy, and find two effects with opposite signs. Moreover, they find that those countries with smaller, more efficient bureaucracies are likely to protect intellectual property more effectively. Finally, they show that the spread of access to the Internet is negatively correlated with the software piracy rate.
Keywords: K42; L86; O3; O57; 330; piracy rate; education; R&D; quality bureaucracies; intellectual property; Internet